Making molecules by mergoassociation: The role of center-of-mass motion - Robert C. Bird; Jeremy M. Hutson (Physical Review Research)
In mergoassociation, two atoms in separate optical traps are combined to form a molecule when the traps are merged. Previous theoretical treatments have considered only the relative motion of the atoms, neglecting coupling to the motion of the center of mass. We develop a theoretical method to include the coupling to center-of-mass motion and consider its consequences for experiments for both weak and strong coupling. We consider the example of RbCs and then extend the treatment to other systems where mergoassociation may be effective, namely RbSr, RbYb, and CsYb. We consider the role of the coupling when the traps are anisotropic and the potential use of movable traps to construct quantum logic gates.